Lemongrass (Cymbopogon citratus) Essential Oil: Extraction, Composition, Bioactivity and Uses for Food Preservation – a Review - Ewa Majewska; Mariola Kozłowska; Eliza Gruczyńska-Sękowska; Dorota Kowalska; Katarzyna Tarnowska (Polish Journal of Food and Nutrition Sciences)
Lemongrass essential oil comes from the lemongrass plant ( Cymbopogon citratus ), which grows mainly in tropical and subtropical parts of the world. The prefix ‘lemon’ indicates its typical lemon-like odour, which is caused mainly by the presence of citral. Citral is a combination of two stereoisomeric monoterpene aldehydes; the trans isomer geranial is in predominance to the cis isomer neral. Lemongrass essential oil has been used since ancient times in folk medicine as a remedy to improve circulation, stabilise menstrual cycles, promote digestion or increase immunity. It is also used to produce perfumes, flavours, detergents, and pharmaceuticals. The method found to be the most suitable for the extraction of lemongrass essential oil is steam distillation, since it allows obtaining the oil without altering product quality. The chemical composition of the essential oil of C. citratus varies according to the geographical origin, farming practices, plant age, photoperiod, harvest period, genetic differences, and extraction methods. The chemical constituents of the essential oil which have constantly been detected and determine its biological activity are aldehydes, hydrocarbon terpenes, alcohols, ketones, and esters. The lemongrass essential oil shows a wide spectrum of biological activities. High antibacterial and remarkable antifungal activities make the lemongrass oil a potential food preservative. This paper reviews recent information on extraction methods of lemongrass essential oil, its chemical composition depending on the origin of the plant, bioactivity of the oil constituents as well as potential application as a food preservative.